CONSEQUENCES OF THE NON-EXISTENCE OF THE "SEP" COMPONENT FOR NOBLE GAS GEO-AND COSMOCHEMISTRY - Wieler R.; Grimberg A.; Heber V.S. (My University, 2007)
Lunar and asteroidal regolith samples irradiated by the solar corpuscular radiation have long been thought to contain two isotopically distinct components of solar noble gases, the well-known solar wind close to grain surfaces and a component implanted with higher energies and thus dubbed "SEP" (for solar energetic particles) at slightly larger depth. The apparently large abundance of the "SEP" component has always been very difficult to understand, however. Recently, depth profiles of the isotopic composition of implanted solar Ne into a special target exposed on NASA's Genesis space mission have unequivocally shown that the depth profiles in the Genesis target and also the extraterrestrial samples can be explained by a depth-dependent isotopic fractionation of the implanted solar wind (A. Grimberg et al., Science 314, 1133-1135, 2006). Hence, "SEP" as isotopically distinct component in extraterrestrial samples does not exist. This contribution discusses some consequences of the elimination of "SEP" from the "noble gas alphabet" for geo-and cosmochemistry. © 2007 Elsevier B.V. All rights reserved.
Keywords: NOBLE GASES; SEP; SOLAR WIND